Pengelolaan Tenaga Kerja Di Pt. Garam Jaya (studi kasus PT. Garam Jaya Desa Muara Baru Kec. Cilamaya Wetan. Kabupaten Karawang) - Reni Tri Lestari; Enjang Suherman (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research examines workforce management at PT. Garam Jaya, a salt producing company in Karawang which still uses traditional production methods. This study aims to understand the challenges faced in workforce management and provide recommendations to improve efficiency and productivity. The method used is descriptive with an observational approach, where participants directly observe the production process and labor interactions in the factory. The results of the visit showed low motivation of the workforce due to the lack of modern facilities and a monotonous work environment. To overcome this problem, improving work welfare and developing intensive training programs is recommended. In conclusion, equipment modernization, improving employee welfare, and ongoing training programs are very necessary to improve performance and production efficiency at PT. Garam Jaya.